3D Hydrogels: Capillary Origami Inspired Fabrication of Complex 3D Hydrogel Constructs (Small 33/2016). Issue 33 (September 2016) - Li, Moxiao; Yang, Qingzhen; Liu, Hao; Qiu, Mushu; Lu, Tian Jian; Xu, Feng
Abstract : A facile method for fabrication of complex 3D hydrogel constructs is developed by T. J. Lu, F. Xu, and co‐workers on page 4492. Built upon capillary origami, well‐controlled hydrogel structures with programmable shapes and sizes are produced by crosslinking during folding process. The profiles of the structure are dependent on crosslinking time, properties of the membrane and liquid, and the membrane shape. This method holds great potential to be high‐throughput and applicable to various materials.